Approaching Crisis of Global Cooling and the Limits to Growth—Global Warming Is Not Our Future by Shigenori Maruyama - Cranganu, Constantin (Journal of Scientific Exploration, 2013)
I have to confess that, when I received the invitation to review the new book published by Shigenori Maruyama, my first impulse was to quickly search the Internet for more information about him. Why? Because Shigenori Maruyama is not a largely known name in either field of proponents or skeptics of anthropogenically driven global warming. In addition, the author is from Japan (the country where the Kyoto Protocol originated), and I am not familiar with Japanese scientists actively involved in climate change debates. These were my reasons for reviewing the book Approaching Crisis of Global Cooling and the Limits to Growth–Global Warming Is Not Our Future. Shigenori Maruyama is a professor at the Tokyo Institute of Technology and a reputable geologist with important contributions describing the role of superplumes in driving the Earth's mantle geodynamics. His interests in climate change studies have the air of a pioneering work, testing the waters and trying to make a point. This situation has its advantages and pitfalls at the same time. Being a novice in the field of climatology, someone may enjoy the status of a candid person, without an agenda. His views are like fresh air in a suffocating arena. At the same time, the lack of credentials in the same field (just one publication in 2008) may jeopardize the credibility of his views which have not been peer-reviewed and accepted in the specialty literature. After a Prologue that sets the coordinates of the entire book, Professor Maruyama exposes The Crazy Concert of Global Warming (Chapter 1) that started, according to him, with "the sensational Inconvenient Truth" (it is more correct to say "An Inconvenient Truth"). Next, we are presented with, among other things, the "Origin of the Theory of Criminality of Carbon Dioxide" which is going to be demolished in Chapter 2, Collapse of the Theory That Carbon Dioxide Is the Criminal. The refutation is invoking well-known arguments, such as sun spots, cosmic rays, geomagnetism, volcanic activity, or Milankovitch cycles (the author or translators write "Milankovitch cycle," which is incorrect, because there are three Milankovitch cycles, not only one). This chapter contains the direst prediction in the entire book: "It is considered that the atmospheric temperature will meet the lowest value for the last one hundred years in 2035 when the solar activity will come to the bottom of the valley" (p. 50), after which "the food production will surely decrease." This means that we have only 22 years left to deal with the cooling climate apocalypse!